Unity for Kant's Natural Philosophy. Issue 3 (July 2014) - Stan, Marius
Abstract : I uncover here a conflict in Kant's natural philosophy. His matter theory and laws of mechanics are in tension. Kant's laws are fit for particles but are too narrow to handle continuous bodies, which his doctrine of matter demands. To fix this defect, Kant ultimately must ground the Torque Law; that is, the impressed torque equals the change in angular momentum. But that grounding requires a premise—the symmetry of the stress tensor—that Kant denies himself. I argue that his problem would not arise if he had kept his early theory of matter as made of mass points, or "physical monads."